PENENTUAN VALUASI PORTOFOLIO OBLIGASI DENGAN CREDIT METRICS DAN MONTE CARLO SIMULATION - Arief Seno Nugroho; Di Asih I Maruddani; Sugito Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2013)
The capital market is one way to get funding for the company and as a medium to strengthen corporate finance position. One of the instruments that are traded than stocks are bonds. The advantage of this instrument because it is easy and rapid acquisition of funds to beused for the operations of the corporate and the period of payment is longer. Bond investment must be noticed valuations and credit risk, with calculating the valuation can be estimate bonds credit risk. Credit Metrics is a reduced form model to estimate the risk of displacement of ratings. The risk not only occur when corporate rating be default but also if the rating upgrade or downgrade. For the determination of the portfolio valuation can be used Monte Carlo simulation using generate scenarios corporate ratings. Empirical study can be used for three bonds there are Obligasi II Bank Danamon Tahun 2010 Seri B, Obligasi II Telkom Tahun 2010 Seri A, and Obligasi Indofood Sukses Makmur V Tahun 2009. Each has an average valuation of 1.013,039 billion, 1.179,203 billion and 2.259,284 billion. The valuation of the portfolio amounted to 4.451,52 billion and a standard deviation 70,33 billion